Size does matter: large-race Bullfinches Pyrrhula pyrrhula pyrrhula dehusk sunflower Helianthus annuus seeds at twice the rate of small-race P.p. coccinea individuals. Issue 2 (1st December 2016) - Fox, Anthony D.; Balsby, Thorsten J.S.
ABSTRACT: Individual consumption rates of sunflower Helianthus annuus seeds were measured among five wild, free-living, colour-marked Bullfinches of the large, nominate race ( Pyrrhula p. pyrrhula ) and 13 individuals of the smaller race ( P.p. coccinea ) during 68 feeding bouts at a Danish feeding station on six dates between 15 December 2005 and 22 January 2006. Based on results from linear mixed models, large-race Bullfinches were twice as adept (mean 11.95 seeds/min) at dehusking and consuming sunflower seeds compared to small-race birds (5.99 seeds/min). We found no effect of age or sex on consumption rates, or any changes in individual performance over time. The relative inefficiency of foraging by local small-race Bullfinches not only results in nutritional intake rates from the same food source that are lower than for the invasive large race but also may potentially increase predation rates, because of the need for prolonged foraging periods in an environment that exposes them to predators.